Deltamethrin residues in imported and locally produced butter, cream and soft cheese in the south of Baghdad city: Najim Hadi Najim and Amel Hussein Ali - Ali, Amel Hussein (The Iraqi Journal of Veterinary Medicine, 2017)
A total of 40 imported cream, butter, cheese and yoghurt samples were collected randomly at weekly intervals (1samples/ product/ week) from various supermarkets inside the Baghdad province during the summer period. A total of 84 samples of locally produced cream, Butter, soft cheese and yoghurt that belonged to buffaloes, cows and ewes were collected randomly at weekly intervals (1 sample/ product/ week) from three different townships (Al-mahmudiyah, Al-Rasheed and Al-latifiyah) and were examined on two periods, the first was the period that extended from the beginning of September to the end of November 2015 while the second was the period that extended from the beginning of January to the end of march 2016. Besides that 12 Buffalos̓ raw whole and skimmed milk samples (6 samples each) and 6 samples of locally produced ewes̓ ghee (Samna) were examined during the summer period. Each dairy product sample was tested for the occurrence of Deltamethrin residues by using the High Performers liquid Chromotography and for fat content by using Gerber method. From the obtained results, data revealed that all of the imported cheese, cream and butter samples were 100% positive and yoghurt samples were 60% positive for the occurrence of Deltamethrin residues during the summer season. The results of this study established the statistically significant (P<0.05) influence of the season on the concentrations of the Deltamethrin residues in all of the examined locally produced dairy products where it was found that each of the 7 locally produced dairy products samples (6 samples/ each product) had significantly (P<0.05) higher concentrations of Deltamethrin residues in summer than in winter seasons. All the examined locally produced dairy products except yoghurt during the summer season presented high contamination levels with Deltamethrin residues and were 100% above the Maximum Residue Limits of 0.05 ppm that recommended by the WHO, FAO and European legislation.